2004
DOI: 10.1111/j.1365-2028.2004.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the biology of Nile tilapia, Oreochromis niloticus L., in two Ugandan crater lakes

Abstract: In this study, we compare the diet, life history characters and abundance of Nile tilapia (Oreochromis niloticus) stocks between two crater lakes in western Uganda (Lake Nyamusingiri and Lake Kyasanduka) that differ in their history of fishing pressure. Both lakes support native fish communities, but also harbour populations of introduced O. niloticus. Lake Nyamusingiri was characterized by a higher relative and absolute abundance (CPUE) of haplochromine cichlids and a lower abundance of O. niloticus than in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 15 publications
(16 reference statements)
5
48
0
Order By: Relevance
“…Condition factor K has been associated to other factors, including fish abundance and competition in ecosystems (Balirwa 1998;Bwanika et al 2004;Otieno et al 2013). For example, Balirwa (1998) reported that with declining fish populations in Lakes Kyoga and Victoria, less competition for food resources could have led to improvement of K values.…”
Section: Discussionmentioning
confidence: 99%
“…Condition factor K has been associated to other factors, including fish abundance and competition in ecosystems (Balirwa 1998;Bwanika et al 2004;Otieno et al 2013). For example, Balirwa (1998) reported that with declining fish populations in Lakes Kyoga and Victoria, less competition for food resources could have led to improvement of K values.…”
Section: Discussionmentioning
confidence: 99%
“…Another common sign for the occurrence of overfishing is a reduction in the mean length of fishes in the catch [27]. Stunting or dwarfing of tilapia is a common phenomenon whenever there is high fishing pressure [39]. In line with this pattern, also the tilapia of Lake Hawassa is becoming stunted and matures at a smaller size.…”
Section: Page 8 Of 10mentioning
confidence: 90%
“…Stunting or dwarfing of tilapia can also be a sign of overexploitation [8,27,39] in the southern fishery. Length at first sexual maturity of tilapia in Lake Hawassa is 18 cm [40].…”
Section: Page 8 Of 10mentioning
confidence: 99%
“…In studies where the inundation of the margins of African lakes by flood waters has occurred, the combination of decaying submerged terrestrial vegetation and the increased fluvial input of nutrients has resulted in increased production of detritus, phytoplankton, periphyton and zooplankton (Weyl 2007), with phytoplankton production also enhanced by the decreased turbidity (Guenther and Bozelli 2004). In response to the inundation and increased food resources, production of the tilapia species increases (McKaye et al 1995;Bwanika et al 2004;Njiru et al 2004;Peterson et al 2004Peterson et al , 2005Britton et al 2009). Increased growth rate and recruitment success following flood events have also been generally observed in cichlid populations (Dudley 1975(Dudley , 1979De Silva 1985;Weyl 2007) and appears evident in Lake Naivasha (Britton and Harper 2008).…”
Section: Discussionmentioning
confidence: 99%